INFOGRAPHIC MEDIA AND INNOVATIVE LEARNING VIDEOS FOR TEACHING WRITING SCIENTIFIC ARTICLES - Vera Kristiana (IKIP Siliwangi, 2024)
This research examines the application of infographic media and innovative learning videos as an effort to improve the English language scientific article writing skills of students at Harapan University, Medan. Infographics are information media presented in text form, and combined with several visual elements such as images, illustrations, graphs and so on. The advantage of infographic learning media is that it has an attractive appearance, so learning is not boring. It helps students to know what being studied. Infographics and innovative learning videos are the right solution to overcome the problems faced by Harapan University Medan students who are often bored and not enthusiastic about following the learning process, especially regarding English. Quasi Experimental type (quasi-experiment) using Non-equivalent Control Group Design was used in this research. Today's students have experienced a lot of lagging behind, especially in terms of techniques for writing good and correct scientific papers. In fact, this need must always be realized in empowering students for the benefit of society. Therefore, students must be given sufficient provisions in order to prepare for their future, especially in scientific transformation related to good and correct scientific writing techniques.